Vanishing wildlife of North America - Allen, Thomas B; National Geographic Society (U.S.). Special Publications Division ([Washington] [National Geographic Society], 1974)
The vanishing wildlife of North America, where you can find help in locating them
The cost of conquest: a continent transformed -- "There is no Ark this time": dilemmas of the lists -- The gunner's targets: game species and game harvest -- "We're going to lose some ..." -- The economics of extinction -- Besieged strongholds of life: disruption and defense -- Warning to an endangered species
"Prepared by the Special Publications Division, National Geographic Society."
Includes bibliographical references (page 207)
Keywords: Rare animals -- North America; Wildlife conservation -- North America; Wildlife management -- North America; Wildlife conservation -- North America